2015
DOI: 10.1158/0008-5472.can-14-2291
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Helicobacter pylori Peptidoglycan Enhances NOD1 Activation and Promotes Cancer of the Stomach

Abstract: Helicobacter pylori is the strongest known risk factor for gastric carcinogenesis. One cancer-linked locus is the cag pathogenicity island, which translocates components of peptidoglycan (PGN) into host cells. NOD1 is an intracellular immune receptor that senses PGN from Gram-negative bacteria and responds by inducing autophagy and activating NF-κB, leading to inflammation-mediated bacterial clearance; however chronic pathogens can evade NOD1-mediated clearance by altering PGN structure. We previously demonstr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 37 publications
6
67
0
Order By: Relevance
“…The protective effect has been demonstrated in studies showing that type I interferon responses induced by NOD1 stimulation reduce the level of H. pylori infection (8) and that β-defensin production induced by NOD1 exerts a negative influence on H. pylori survival (38). The reciprocal proinflammatory effect has been shown in studies showing that NOD1 signaling enhances epithelial chemokine responses and that an H. pylori organism bearing a mutation in its NOD1-stimulating peptidoglycan induces decreased inflammation and malignant transformation in vivo (39). These negative and positive effects on H. pylori –induced inflammation, however, are probably independent from the effects of NOD1 on Cdx2 expression reported here, as the latter influences malignant transformation in gastric tissue harboring a chronic and stable infection.…”
Section: Discussionmentioning
confidence: 96%
“…The protective effect has been demonstrated in studies showing that type I interferon responses induced by NOD1 stimulation reduce the level of H. pylori infection (8) and that β-defensin production induced by NOD1 exerts a negative influence on H. pylori survival (38). The reciprocal proinflammatory effect has been shown in studies showing that NOD1 signaling enhances epithelial chemokine responses and that an H. pylori organism bearing a mutation in its NOD1-stimulating peptidoglycan induces decreased inflammation and malignant transformation in vivo (39). These negative and positive effects on H. pylori –induced inflammation, however, are probably independent from the effects of NOD1 on Cdx2 expression reported here, as the latter influences malignant transformation in gastric tissue harboring a chronic and stable infection.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, our laboratory demonstrated that H. pylori apo-AcnB binds to the 3= UTR of the peptidoglycan deacetylase (pgdA) transcript, resulting in transcript stability and increased PgdA expression (5). PgdA confers lysozyme resistance and immune evasion; its expression is increased when H. pylori cells are exposed to oxidative stress or are in contact with host immune cells (19)(20)(21)(22). AcnB plays an important role in the posttranscriptional regulation of PgdA (5).…”
mentioning
confidence: 99%
“…2). 74 Moreover, xenophagy appears to be a pivotal mechanism involved in H. pylori recognition and H. pylori-related gastric cancer. The highly virulent H. pylori strain GC026 that is associated with gastric cancer can markedly downregulate xenophagy in AGS cells.…”
Section: The Role Of Xenophagy In Bacterial-associated Cancermentioning
confidence: 99%